Analisis Implementasi Pembiayaan Pertanian Berbasis Akad Murabahah Dan Ijarah Dalam Persfektif Fiqih Muamalat Dan DSN-MUI - Sri Wahyuningsih; Ari MH; Andi Suhandi; Azmy MH; Vanya Agustalita (LPPM STEBIS YPII, 2024)
This research is motivated by the presence of Islamic-based financial institutions, including non-bank financial institutions. One of them is Baitul Maal wat Tamwil (BMT). The financial product used by BMT in agriculture is financing based on trade principles (murabahah). Murabaha is a trade agreement for certain products that clearly determines which products the seller buys and sells, including the price of the product that is sold to the buyer, and then makes a profit. The topic that the researchers will discuss is how the implementation of murabahah and ijarah financing for the financing of the agricultural sector at BMT UGT Sidogiri, Cikarang Pusat. This research uses qualitative research, for data collection using three methods: observation, interviews, and documentation which is carried out directly at the BMT UGT Sidogiri Cikarang Pusat office with the head of the BMT branch as the main informant. Based on the results of the study, it can be concluded that financing in the agricultural sector of BMT UGT Sidogiri Cikarang Pusat uses murabahah and ijarah contracts, where the murabahah contract is used to meet the needs of goods, buy agricultural machinery and agricultural production facilities. While the ijarah contract is used to finance land leases.